Evaluasi Pembelajaran Pendidikan Agama Islam Dalam Membentuk Karakter Religius Peserta Didik di Era Digital - Fikriyanti Putri Pratama; Apri Muliana; Shofia; Muh. Anwar Abdullah; Ahmad Fauzan; Risma Handayani (NAAFI: JURNAL ILMIAH MAHASISWA, 2026)
The advancement of digital technology has increased the need for an Islamic Religious Education (IRE) learning evaluation system that is capable of assessing not only students’ cognitive achievement but also the development of their religious character. This study aims to analyze the implementation of IRE learning evaluation in promoting students’ religious character in the digital era, as well as to examine the challenges encountered and strategies for improving the effectiveness of the evaluation process. This research employed a qualitative approach using the library research method. Research data were collected from relevant books, scholarly articles, and documentary sources, and analyzed using content analysis. The findings indicate that IRE learning evaluation, which applies various assessment methods such as observation, attitude assessment, portfolios, project-based assignments, and self-reflection while covering cognitive, affective, and psychomotor domains, positively contributes to the formation of students’ religious character. However, several challenges remain, including exposure to inappropriate digital content, limitations in monitoring students’ behavior outside the school environment, and insufficient digital literacy. Therefore, active collaboration among teachers, parents, and schools is essential to effectively develop students’ religious character and optimize IRE learning evaluation in the digital era.